SIX YEARS OF SUMMER SCIENCE INSTITUTES IN INDIA: A PROGRAM THAT HAS SUCCEEDED. - Bingham, N. Eldred (Science Education, 1969)
The article focuses on the introduction of the Summer Institutes for the Preparation of Science Teachers in the U.S. In 1963, funds became available through the United States Information Service and were used in the procurement of the texts, laboratory guides, teacher's manuals, resource books, films and laboratory supplies essential to train people to teach new science and mathematics programs that had been develop in the country. The cooperative effort of the U.S. and Indian personnel in organizing and conducting institutes for science teachers has improve the course in India.